2020
DOI: 10.1108/nfs-07-2020-0282
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diets are detrimental of the lipid profile, glucose metabolism and body composition of Wistar rats: the role of fatty acid type and consumption duration

Abstract: Purpose The purpose of this study is to evaluate the nutritional effects in Wistar rats of supplementation with stand-alone saturated fatty acid (SFA) or monounsaturated fatty acid (MUFA), the replacement of SFA by MUFA and the combination of both (SFA + MUFA) over a long period of time (13 weeks). Design/methodology/approach In total, 30 Wistar rats were used and randomly assigned to receive (n = 6): control – lab chow; lard (L20%) – lab chow with added lard (20%); olive oil (O20%) – lab chow with added oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Similarly, Kang et al (2008) reported that consumption of 3% raw garlic and feed containing BG did not affect the BW of rats fed with 1% cholesterol. When high fat is consumed in excess and chronically, both types of saturated fatty acid and unsaturated fatty acid can produce deleterious effects on the serum lipid profile and abdominal fat accumulation, also increasing the TG/HDL-c ratio (Rocha-Gomes et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kang et al (2008) reported that consumption of 3% raw garlic and feed containing BG did not affect the BW of rats fed with 1% cholesterol. When high fat is consumed in excess and chronically, both types of saturated fatty acid and unsaturated fatty acid can produce deleterious effects on the serum lipid profile and abdominal fat accumulation, also increasing the TG/HDL-c ratio (Rocha-Gomes et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To prepare the diets, the lab chow (Nuvilab ® CR‐1) was previously ground and added with lard (Seara ® ) and/or unripe banana flour. After, they were processed in a mixer to ensure homogenization and stored in a refrigerator (0 ± 2°C) (Rocha‐Gomes et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The TG/HDL‐c ratio was calculated to estimate the cardiovascular risk (Alsina et al, 2016). In addition, the technique of Folch et al (1957) and Labtest ® kits (Rocha‐Gomes et al, 2020) were used to measure the levels of cholesterol and triglycerides in the liver and feces.…”
Section: Methodsmentioning
confidence: 99%